Perbedaan Tingkat Kecemasan Antara Siswi Kelas 1 Dan Siswi Kelas 2 Mts di Pondok Pesantren Modern Islam Assalaam Sukoharjo - Wibowo, Puspo Ari, dr. Adriesti Herdaetha, Sp.KJ, M.H (2017)
Background: Anxiety is emotionalsubjective conditions such as tension, cares, and fears and also characterized by ctive central nervous system. Anxiety disorders are common in young children and can cause a decline in schoolperformance. Comparison of cases of women and men was 12.6 versus 6.8 cases in 1000 population each year with the number of women at 17.8% and men 9.6% in 1000 population each year. Problems in school adjustment may arise when teens begin new levels of schooling that requires students to live independently, namely the halls of residence. Because it requires a study to determine differences in the level of anxiety among students according to the length stay in the dorm, so that anxiety can be avoided or even in use as motivation to increased student achievement.Aim: To determine differencesanxiety level of Assalaam Islamic Boarding School according to the length of stay in the dorm, especially 1st grade and 2nd grade MTs.Metode : Research conducted including analytic descriptive research using cross sectional method to measure anxiety levels both groups simultaneously. Identification to measure the level of confidence of respondents using questionnaires Lie Minnesota Multiphasic Personality Inventory (MMPI-L), and continue using TMAS (Taylor Manifest Anxiety Scale) to measure the level of anxiety. Grade 1 and 2 MTs are invited to fill out questionnaires and TMAS LMMPI. Of the total 45 samples representing each group.Results: the mean anxiety score 1st grade higher then 2nd class by 5:02 point and compared The test results independent sample t test showed that there are differences between the mean scores of anxiety among the group of children grader in 1 MTs with 2 MTs. Statistically differences are so significant with p = 0.000.Conclusion: This study concluded that there are different levels of anxiety between 1st grade and 2nd grade MTs in Assalaam Modern Islamic Boarding School Sukoharjo According To The Length Stay In Dorm.